Youth in Saudi Arabia - Fadaak, Talha H.; Roberts, Ken (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book uses the youth life stage as a window through which to view all domains of life in present-day Saudi Arabia: family life, education, the impact of new media, the labour market, religion and politics. The authors draw extensively on their interviews with 25-35 year olds, selected so as to represent the life chances of males and females who grow up in different socio-economic strata, and typically face different futures. The book presents an account of the ways in which family life, education, religion, employment and the housing regimes interlock, and how and why this interlocking is subject to increasing stresses. The chapters, which are built on documentary research, official published statistics and the authors' original evidence, provide invaluable insights into Saudi youth, which has never before been examined in such depth. Youth in Saudi Arabia will be of interest to students and scholars across a range of disciplines including Sociology, Politics and Middle East Studies.